Immunohistochemical localization of nitric oxide synthase (NOS) isoforms in epidermis and gill epithelium of an angler catfish, Chaca chaca (Siluriformes, Chacidae). (December 2018) - Mistri, Arup; Kumari, Usha; Mittal, Swati; Mittal, Ajay Kumar
Graphical abstract: Highlights: NOS isoforms were localized immunohistochemically in epidermis and gill epithelium of C. chaca . nNOS + ve cells were discernible in outer layers of epidermis and epithelium of gill filaments. iNOS + ve cells were observed in different layers of epidermis and outer layers of gill filaments and lamellae. eNOS + ve cells were identified in outer layers of epithelium of gill filaments and secondary lamellae. Expression of NOS isoforms could be associated with their role in relation to the physiology of fish. Abstract: The present study is concerned with the expression and localization of nitric oxide synthase (NOS) isoforms, nNOS, eNOS and iNOS in the epidermis and the gill epithelium of Chaca chaca by means of immunohistochemical techniques. nNOS immunoreactivity was observed in the outer layer epithelial cells of the epidermis, outer epithelium of gill filaments at their distal regions and in between the secondary lamellae. iNOS positive cells were observed at intervals in the epidermis from basal layer to superficial layer, in outer layers of epithelium of the gill filament and in epithelium of the secondary lamellae. The expression of eNOS is similar to that of iNOS in the gills. In addition, NOS activity was also observed in the taste buds in the epidermis. The expression of different NOS isoforms in C. chaca are associated to increase the adaptability and survivability of the fish in hypoxic condition, help in defence and ion regulation and sensory functions. The study could be useful to understand the expression of NOS isoforms in different fish tissues and their diverse role in relation to the physiology of the fish.